Characterization of the Ovarian Development and Associated Factors during the Breeding Migration of ICoilia nasus/I in the Yangtze River - Wei, Shuwei; Hua, Zhong; Yang, Yanping; Ma, Fengjiao; Han, Wei; Zhang, Wei; Ying, Congping; Deng, Yanmin; Liu, Kai (Fishes, 2024)
Coilia nasus is a typical anadromous migratory fish found in the lower reaches of the Yangtze River. Every year, C. nasus clusters offshore and swims upstream along the Yangtze River into the tributaries and lakes in the middle and lower reaches of the Yangtze River to breed. In this study, female C. nasus were collected as study subjects from the Chongming section of Shanghai, the Taizhou section of Jiangsu, and the Anqing section of Anhui. Their ovaries were used to examine tissue sections and investigate gene expression, including the follicle-stimulating hormone receptor (fshr), the luteinizing hormone receptor (lhr), kisspeptin-1 (kiss1), and forkhead box l2 (foxl2), which are related to reproductive development, while the serum levels of estrogen (including estradiol, E2) and progestins (including 17α,20β-dihydroxy-4-pregenen-3-one, 17α,20β-DHP) were also analyzed. Our results showed that, first, the growth period of the oocytes was small in stage II of ovarian development, in which both E2 and 17α,20β-DHP levels and gene expression were low. Then, in stage III, the growth period of the oocytes became large, and the yolk granules and oil droplets began to appear. Simultaneously, E2 and the expression of kiss1 and foxl2 were significantly elevated. Finally, stage IV was the period of a large amount of accumulation of nutrients in the oocytes, and 17α,20β-DHP levels and the expression of fshr and lhr were significantly elevated. These results enrich the theoretical study of ovarian development in the natural population of C. nasus, supplementing the biological basis of C. nasus reproduction and scientifically supporting the study of C. nasus population ecology and resource conservation.